Complete elimination of methane formation in stored livestock manure using plasma technology - Nyvold, Magnus; Dörsch, Peter (Frontiers in Sustainable Food Systems, 2024)
Plasma-based nitrogen fixation has recently been shown to be applicable in the domain of manure management, as it has the ability to reduce ammoniacal nitrogen losses and increase the nitrogen content of organic wastes, with air and electricity as the only input. In addition, the plasma treatment confers antimicrobial properties, which we hypothesize to be transferable to methanogenic archaea and hence prevent methane formation during manure storage – a major contributor to global anthropogenic greenhouse gas emissions. In this work we compared the methane formation from cow manure to the methane formation in nitrogen enriched cow manure, kept in two outdoor storage tanks for 70–80 summer days over three consecutive years. In all instances, the methane formation was eliminated completely. To investigate the cause of inhibition, a controlled incubation experiment was conducted to show that neither the acidification nor the addition of nitrate or nitrite, alone or in combination, could explain the inhibition of methanogenesis and denitrification that occurred in plasma treated cow manure at moderate pH.